Cardiac involvement in Wilson disease: Review of the literature and description of three cases of sudden death. Issue 5 (2nd August 2021) - Chevalier, Kevin; Benyounes, Nadia; Obadia, Michaël Alexandre; Van Der Vynckt, Clélie; Morvan, Erwan; Tibi, Thierry; Poujois, Aurélia
Abstract: Wilson disease (WD) is a rare genetic condition that results from a build‐up of copper in the body. It requires life‐long treatment and is mainly characterized by hepatic and neurological features. Copper accumulation has been reported to be related to the occurrence of heart disease, although little is known regarding this association. We have conducted a systematic review of the literature to document the association between WD and cardiac involvement. Thirty‐two articles were retained. We also described three cases of sudden death. Cardiac manifestations in WD include cardiomyopathy (mainly left ventricular (LV) remodeling, hypertrophy, and LV diastolic dysfunction, and less frequently LV systolic dysfunction), increased levels of troponin, and/or brain natriuretic peptide, electrocardiogram (ECG) abnormalities, and rhythm or conduction abnormalities, which can be life‐threatening. Dysautonomia has also been reported. The mechanism of cardiac damage in WD has not been elucidated. It may be the result of copper accumulation in the heart, and/or it could be due to a toxic effect of copper, resulting in the release of free oxygen radicals. Patients with signs and/or symptoms of cardiac involvement or who have cardiovascular risk factors should be examined by a cardiologist in addition to being assessed by their interdisciplinary treating team. Furthermore, ECG, cardiac biomarkers, echocardiography, and 24‐hours or more of Holter monitoring at the diagnosis and/or during the follow‐up of patients with WD need to be evaluated. Cardiac magnetic resonance imaging, although not always available, could also be a useful diagnostic tool, allowing assessment of the risk of ventricular arrhythmias and further guidance of the cardiac workup.